2017
DOI: 10.1038/s41598-017-16519-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field observations in CoFeB/Ta layers with 0.67-nm resolution by electron holography

Abstract: Nanometre-scale magnetic field distributions in materials such as those at oxide interfaces, in thin layers of spintronics devices, and at boundaries in magnets have become important research targets in materials science and applied physics. Electron holography has advantages in nanometric magnetic field observations, and the realization of aberration correctors has improved its spatial resolution. Here we show the subnanometre magnetic field observations inside a sample at 0.67-nm resolution achieved by an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The microstructure of various materials has been widely studied using transmission and analytical electron microscopy [ 1–10 ], and electric and magnetic fields both inside and outside materials have been investigated using Lorentz transmission electron microscopy [ 11 ], differential phase contrast scanning electron microscopy [ 12 , 13 ] and electron holography [ 14–24 ]. The magnetic flux distribution and domain structure of various magnetic materials have been successfully analyzed with these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure of various materials has been widely studied using transmission and analytical electron microscopy [ 1–10 ], and electric and magnetic fields both inside and outside materials have been investigated using Lorentz transmission electron microscopy [ 11 ], differential phase contrast scanning electron microscopy [ 12 , 13 ] and electron holography [ 14–24 ]. The magnetic flux distribution and domain structure of various magnetic materials have been successfully analyzed with these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…To realize high-resolution magnetic field observations, a pulse magnetization system was developed to reverse the magnetization in the sample without changing the geometrical configuration of the sample holder and stage referring to the electron beam. Using this system, the magnetic fields in CoFeB/Ta layers were observed at 0.67-nm resolution [3]. However, due to the experimental residual aberrations, the atomic-resolution has not been achieved.…”
mentioning
confidence: 99%
“…Electron holography allows direct access to the Aharonov-Bohm phase by interfering a reference wave with part of the wave that passed the magnetic object, using a biprism [60,[227][228][229]. Recently, it has been demonstrated that electron holography is capable of resolving magnetic field in a CoFeB/Ta multilayer sample with sub-1 nm resolution [42,230].…”
Section: Beyond Fresnel Imagingmentioning
confidence: 99%
“…The study of the dynamics involved in the manipulation of nanoscale magnetic textures demands experimental methods with sufficient spatiotemporal resolution. Based on transmission electron microscopy (TEM), Lorentz microscopy [39][40][41] is an established method for the static imaging of nanoscopic magnetic structures, capable of resolving magnetic features < 1 nm [42]. While early attempts of time-resolved Lorentz microscopy do exist, these fell short in providing the spatial resolution achievable in static measurements [43,44].…”
Section: Introductionmentioning
confidence: 99%